2004
DOI: 10.1016/j.molcel.2004.11.013
|View full text |Cite
|
Sign up to set email alerts
|

PHAX and CRM1 Are Required Sequentially to Transport U3 snoRNA to Nucleoli

Abstract: To better understand intranuclear-targeting mechanisms, we have studied the transport of U3 snoRNA in human cells. Surprisingly, we found that PHAX, the snRNA export adaptor, is highly enriched in complexes containing m7G-capped U3 precursors. In contrast, the export receptor CRM1 is predominantly bound to TMG-capped U3 species. In agreement, PHAX does not export m7G-capped U3 precursors because their caps become hypermethylated in the nucleus. Inactivation of PHAX and CRM1 shows that U3 first requires PHAX to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
204
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(220 citation statements)
references
References 32 publications
12
204
0
1
Order By: Relevance
“…Importantly, similar Crm1-containing bodies associated with nucleoli (CNoBs) were present in untransfected cells. In some cells, beside this localization, Crm1 was also enriched in bodies distant from nucleoli, in agreement with a previous report that Crm1 is a component of Cajal bodies (Boulon et al, 2004).…”
Section: Cpeb1 Foci Colocalize With Crm1supporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, similar Crm1-containing bodies associated with nucleoli (CNoBs) were present in untransfected cells. In some cells, beside this localization, Crm1 was also enriched in bodies distant from nucleoli, in agreement with a previous report that Crm1 is a component of Cajal bodies (Boulon et al, 2004).…”
Section: Cpeb1 Foci Colocalize With Crm1supporting
confidence: 92%
“…This default is associated with defective pre-40S export. Interestingly, A0 cleavage requires the snRNA U3, and LMB has been shown to prevent the routing of U3 from Cajal bodies, where it is processed, to the nucleolus (Boulon et al, 2004). In this context, CNoBs could also be a platform for processing factors.…”
Section: Role Of Cnobsmentioning
confidence: 99%
“…This modification is recognized by Snuportin-1 in association with Importin-β and other factors to import the snRNAs back into the nucleus (30,31). Interestingly, Exportin-1 also has high affinity for the (TMG)-capped small nucleolar RNA (snoRNA) U3 in the nucleus and transports it from Cajal bodies to the nucleoli (32). Another study showed that TGS1 enhances Rev-dependent HIV-1 RNA expression by (TMG)-capping viral mRNAs in the nucleus, thereby increasing recognition by Exportin-1 for transport to the cytoplasm (33).…”
Section: Significancementioning
confidence: 99%
“…31,32 Recent work showed that coilin directly binds snoRNAs 33 and that snoRNAs shuttle via CBs before they reach their nucleolar destination. 33,34 Therefore it is tempting to speculate that snoRNP assembly, like snRNP assembly, takes place in CBs and that coilin plays an important role as well.…”
Section: Coilin Historymentioning
confidence: 99%